Localisation of a Global Brand Campaign : Case Study of Durex “Real Feel” - Bestová, Dominika (2016)
This bachelor thesis introduces in the beginning the basic theory of marketing and brands. The main topic there is the debate of standartization against local adaptation of marketing activities in the environment of global markets. The practical part then presents a case study of Durex brand, where a centrally developed campaign Real Feel was localized for needs of the United Arabic Emirates market.